CAUSE OF CONTRACTUAL OBLIGATIONS AS A PRECONDITION OF THE VALID FORMATION OF THE MUTUALLY BINDING CONTRACT - Manić, Samir O (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
Under the influence of the French Civil Code, our legal order also became one of the causal legal orders. The basic and most important provisions on the cause are in the articles of the Law on Obligations (ZOO) which refer to the basis of the contractual obligation and the motive for concluding the contract. Namely, our ZOO has adopted the so-called objective-subjective understanding of the cause. Perhaps a lot was expected from the cause of the contractual obligation in the objective sense, but its inclusion in the line of presumptions of the valid formation of the contract had almost no effect on court practice, so the question justifiably arises why?